Prohibition on Confiscation of State-Owned Immovable Property Against Decisions of the State Administrative Court That Have Already Become Final - Oktapani, Silm; Libra, Robert; Noerdin, Zulkarnaen (Civiliza Publishing, 2024)
State Administrative Law gives the state the right to resolve administrative disputes at the PTUN. However, this is different when faced with the problem of state property, especially state land, which in Article 50 of Law No. 1 of 2004 concerning State Treasury is actually prohibited regarding confiscation of state property including state-owned land. The formulation of this research are: 1) How is the Implementation of the Prohibition of Confiscation of Immovable State Property Against Inkracht State Administrative Court Decisions; and 2) How are the obstacles to the Implementation of the Prohibition of Confiscation of Immovable State Property Against Inkracht State Administrative Court Decisions. The research method used is Normative law. The results and discussion found that the implementation of the PTUN's decision regarding the confiscation of state property is hindered by the provisions of Article 50 paragraph (1) of Law No. 1 of 2004 concerning State Treasury so that the provisions need to be changed. Then, the obstacle that arises in terms of implementing the decision is the absence of a process that binds state officials or bodies to comply with the PTUN decision in Law No. 5 of 1986 concerning State Administrative Court. This is in fact very contrary to the principle of legal objectives desired by Gustav Radbruch who mentioned 3 (three) legal objectives, namely legal certainty, legal benefits, and legal justice. Therefore, it is necessary to amend the provisions of Law No. 1 Year 2004 on State Treasury and Law No. 5 Year 1986 on Administrative Court to accommodate the decision of the Administrative Court to execute state property.